A national and local media perspective on responsibility for and solutions to storm-related power outages in the northeastern United States. (27th May 2019) - Kloster, Danielle P.; Morzillo, Anita T.; Volin, John C.
ABSTRACT: Major storms in the northeastern United States in 2011 and 2012 caused widespread power outages, bringing attention to the vulnerability of utility infrastructure as a result of extreme weather and environmental change. Media coverage of such focusing events provides context for and can affect government and public response. Our objective was to analyze gatekeeping, agenda setting, and framing in the New York Times (NYT) and local newspapers covering power outages related to large storm events in 2011 and 2012 (Tropical Storm Irene, October snowstorm, Hurricane Sandy). Government and utility officials focused on structural solutions to mitigate future storm impacts, whereas residents and businesses targeted individual actions. NYT interviews included residents more frequently than local newspapers, influencing coverage of impacts and solutions. Geographic differences between NYT and local newspapers' foci may relate to coverage of solutions to and responsibility for outages. Our findings demonstrate the importance of collective action toward shared solutions.